The relationship of strategic improvisation, entrepreneurial marketing and social capital in the small-scale business performance and the moderating role of government support - Rabitah, Harun (2022)
Business performance has become a broad important area of study amongst social science researchers. Empirical outcomes in the literature suggest various influence factors that may stimulate the firm or organization performance. However, in the current challenging and uncertain business environment, an auxiliary study is beneficial in determining the main success factors, particularly in the context of Small and Medium-sized Enterprises (SMEs). The primary concern of this research was to investigate the relationship between strategic improvisation, entrepreneurial marketing, social capital and business performance. In order to improve the outcome of the study, the moderating influence of government support was considered. A quantitative research method was used. 13 hypotheses were proposed and the framework was investigated using the underpinning theory of the Research Based View (RBV). A number of 213 registered Agrobazaar Kedai Rakyat (AKR) entrepreneurs were the respondents in this study. Data was collected using a structured self-administered questionnaire and the research covered 14 states in Malaysia. SPSS version 24 was used to analyse this research model for screening and descriptive data analysis. Then, inferential analysis was performed using the Smart Partial Least Squares (Smart-PLS 3.0) analysis technique. Strategic improvisation was found to be the most important predictor, followed by six (6) dimensions of entrepreneurial marketing and social capital. The findings were significant and they were positively related to business performance. In addition, 11 hypotheses were confirmed to be supported; however, another two hypotheses, and the moderating effect of government support, were found to be significant but negatively moderated the relationship of strategic improvisation and social capital with business performance. Given the importance of strategic improvisation, entrepreneurial marketing, social capital and government support in determining business performance. This research framework appears to be an original and valuable contribution to the body of knowledge that can assist small business entrepreneurs, practitioners, stakeholders, policy-makers, and government agencies in responding to market turbulence.